Method for improving performance and energy efficiency of non-aqueous flow battery by using ultrasound
Intermittent ultrasound application in non-aqueous liquid flow batteries stabilizes electrochemical properties and reduces energy consumption, addressing viscosity issues and enhancing performance and efficiency.
Patent Information
- Application Number
- CN202411347222.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Non-aqueous electrolyte flow batteries face challenges with high viscosity affecting reactive substance transmission and current density, while continuous ultrasound application improves these but reduces energy efficiency due to high energy consumption.
Intermittent application of ultrasound to non-aqueous liquid flow battery electrolytes, with specific pause times to stabilize and recover electrochemical properties, optimizing performance and energy efficiency.
Enhances electrochemical performance and reduces internal resistance, while significantly improving energy efficiency by minimizing ultrasound energy consumption.
Smart Images

Figure CN119208686A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery performance testing, and in particular to a method for improving the performance and energy efficiency of a non-aqueous liquid flow battery by using ultrasound. Background Art
[0002] Non-aqueous electrolyte flow batteries have the advantages of high specific energy, high operating voltage and long life. However, the viscosity of non-aqueous electrolytes is relatively high, which affects the transmission of reactive substances in them and also restricts their operating current density. In previous work, ultrasound was added to non-aqueous electrolyte flow batteries, which greatly improved their current density and power density. However, the continuously running ultrasonic generator consumes a lot of energy, reducing the energy efficiency of the flow battery system. Summary of the invention
[0003] In view of this, the present invention proposes a method for improving the performance and energy efficiency of non-aqueous liquid flow batteries using ultrasound to solve the problems existing in the above-mentioned prior art.
[0004] To achieve the above object, the present invention proposes a method for improving the performance and energy efficiency of a non-aqueous liquid flow battery using ultrasound, comprising:
[0005] A non-aqueous liquid flow battery electrolyte is prepared, ultrasound is applied to the non-aqueous liquid flow battery electrolyte for the first time, and the time t1 when the effect of ultrasound on the electrolyte reaches stability is recorded;
[0006] When the ultrasonic effect is stable, the ultrasound is turned off, and the time t2 when the electrochemical properties of the non-aqueous liquid flow battery electrolyte are restored to the state before the application of ultrasound is recorded;
[0007] After recovery, ultrasound is applied again, and the time t3 from the second application of ultrasound to reaching stability is recorded;
[0008] Analyzing the effect of intermittent application of ultrasound on the electrochemical properties of the non-aqueous liquid flow battery electrolyte according to the time t1, time t2, and time t3;
[0009] A comparative experiment of continuously applying ultrasound and intermittently applying ultrasound to the electrolyte of the non-aqueous liquid flow battery is carried out, and the best way to improve the performance of the non-aqueous liquid flow battery is analyzed based on the experimental results.
[0010] Furthermore, the time t2 for the electrochemical performance of the electrolyte of the non-aqueous flow battery to recover to the state before the application of ultrasound is greater than or equal to the time t1 for the effect of ultrasound on the electrolyte to reach stability.
[0011] Furthermore, the types of the non-aqueous liquid flow battery electrolyte include FeCl3DES electrolyte and VCl3DES electrolyte.
[0012] Further, the electrolyte components of the non-aqueous flow battery electrolyte include choline chloride and ethylene glycol;
[0013] Place choline chloride and ethylene glycol weighed in proportion on a heated magnetic stirrer, stir continuously at a constant temperature until the solution becomes clear and transparent, and cool to room temperature in a sealed state;
[0014] The amount and concentration of the electrolyte are set according to the type of non-aqueous flow battery electrolyte being tested.
[0015] Furthermore, the process of analyzing the electrochemical performance of the non-aqueous liquid flow battery electrolyte according to the time t1, the time t2, and the time t3 includes:
[0016] Obtaining a CV curve of the electrolyte of the non-aqueous liquid flow battery, analyzing the change of the redox reaction rate of the non-aqueous liquid flow battery with the duration of ultrasonic action based on the CV curve, and then obtaining the cause of the change of the electrochemical performance of the electrolyte of the non-aqueous liquid flow battery;
[0017] The relationship between the peak values of the oxidation peak and the reduction peak and the process time during the ultrasonic application test is constructed to determine the size of the oxidation peak corresponding to different test times, and then to determine the impact of ultrasound on the electrochemical performance of non-aqueous flow batteries.
[0018] Furthermore, the process of obtaining the CV curve of the non-aqueous liquid flow battery electrolyte includes:
[0019] The surface of the working electrode was polished using aluminum powder with a particle size of 0.2 mm and then rinsed with deionized water;
[0020] Place the electrolytic cell after the electrolyte is prepared in a constant temperature water bath and preheat it to the required temperature for the experiment;
[0021] The scanning interval potential and potential scanning speed were set according to the electrolyte type, the three-electrode system was inserted into the electrolytic cell for CV testing, and the CV curve data was recorded.
[0022] Furthermore, in the process of applying ultrasound to the non-aqueous flow battery electrolyte, a digital thermometer is used to monitor the electrolyte temperature in real time, a water bath method is used to keep the electrolyte temperature constant, and a CV test is performed using an electrochemical workstation and a three-electrode system, wherein the three-electrode system includes a working electrode, a counter electrode, and a reference electrode.
[0023] Furthermore, the process of conducting a comparative experiment of continuously applying ultrasound and intermittently applying ultrasound to the non-aqueous flow battery electrolyte includes:
[0024] The experimental temperature and time are set, and constant current charge and discharge experiments with continuous ultrasound and intermittent ultrasound are carried out on two identical non-aqueous liquid flow batteries using the same positive and negative electrode electrolytes, and energy efficiency data of the non-aqueous liquid flow batteries are obtained respectively. Based on the energy efficiency data, the electrochemical performance of the non-aqueous liquid flow batteries under continuous ultrasound and intermittent ultrasound are compared.
[0025] Furthermore, the experimental equipment of the comparative experiment includes: a graphite felt electrode, a sealing gasket, an ion exchange membrane, and a battery fixture, and a parallel flow field is distributed on the contact surface inside the battery fixture.
[0026] Furthermore, during the comparative experiment, the ion exchange membrane was heated in H2O2 aqueous solution, ultrapure aqueous solution, H2SO4 solution, and ultrapure aqueous solution for 1 hour in sequence, and then immersed in a blank electrolyte for at least 12 hours.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention uses ultrasound to change the mass transfer inside the non-aqueous liquid flow battery, enhance the electrochemical performance, and reduce the internal resistance. A method of intermittently applying ultrasound is further proposed through experiments, which makes the performance improvement effect of the non-aqueous liquid flow battery more significant. At the same time, by setting the ultrasound pause time t2 to be greater than or equal to the ultrasound application time t1, the energy of the applied ultrasound in one cycle can be reduced, thereby improving the energy efficiency of the non-aqueous liquid flow battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0030] Figure 1 This is a schematic flow chart of a method for improving the performance and energy efficiency of a non-aqueous liquid flow battery using ultrasound in an embodiment of the present invention;
[0031] Figure 2 is the polarization curve of the Fe-V redox non-aqueous flow battery at 25°C in an embodiment of the present invention;
[0032] Figure 3 The electrochemical impedance spectra of the FeCl3 electrolyte at different ultrasonic power densities at 25°C in the embodiment of the present invention;
[0033] Figure 4The CV curves of the three processes of the FeCl3 DES electrolyte at 15°C in the embodiment of the present invention and the bar graph of the time required to reach stability, wherein (a), (b), and (c) are the CV curves of the Test, Rest, and Continue processes, respectively, and (d) is a bar graph of the time required to reach stability in the three processes;
[0034] Figure 5 The CV curves of the three processes of the FeCl3 DES electrolyte at 25°C in the embodiment of the present invention and the bar graph of the time required to reach stability, wherein (a), (b), and (c) are the CV curves of the Test, Rest, and Continue processes, respectively, and (d) is a bar graph of the time required to reach stability in the three processes;
[0035] Figure 6 The CV curves of the three processes of the FeCl3 DES electrolyte at 35°C in the embodiment of the present invention and the bar graph of the time required to reach stability, wherein (a), (b), and (c) are the CV curves of the Test, Rest, and Continue processes, respectively, and (d) is a bar graph of the time required to reach stability in the three processes;
[0036] Figure 7 Graphs showing changes in peak values over time during the three processes of Test, Rest, and Continue in the embodiment of the present invention, wherein (a) is the oxidation peak of the Test process, (b) is the reduction peak of the Test process, (c) is the oxidation peak of the Rest process, (d) is the reduction peak of the Rest process, (e) is the oxidation peak of the CONTINUE process, and (f) is the reduction peak of the CONTINUE process;
[0037] Figure 8 The CV curves of the three processes of the VCl3 DES electrolyte at 15°C in the embodiment of the present invention and the bar graph of the time required to reach stability, wherein (a), (b), and (c) are the CV curves of the Test, Rest, and Continue processes, respectively, and (d) is a bar graph of the time required to reach stability in the three processes;
[0038] Fig. 9 The CV curves of the three processes of the VCl3 DES electrolyte at 25°C in the embodiment of the present invention and the bar graph of the time required to reach stability, wherein (a), (b), and (c) are the CV curves of the Test, Rest, and Continue processes, respectively, and (d) is a bar graph of the time required to reach stability in the three processes;
[0039] Fig.10 The CV curves of the three processes of the VCl3 DES electrolyte at 35°C in the embodiment of the present invention and the bar graph of the time required to reach stability, wherein (a), (b), and (c) are the CV curves of the Test, Rest, and Continue processes, respectively, and (d) is a bar graph of the time required to reach stability in the three processes;
[0040] Fig.11 1 is the charge and discharge cycle test result of the Fe-VDES redox non-aqueous flow battery at 25°C in an embodiment of the present invention. DETAILED DESCRIPTION
[0041] Exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to be able to fully convey the scope of the present disclosure to those skilled in the art. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features described in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0042] This embodiment proposes a method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound, such as Figure 1 As shown, including:
[0043] A non-aqueous liquid flow battery electrolyte is prepared, ultrasound is applied to the non-aqueous liquid flow battery electrolyte for the first time, and the time t1 when the effect of ultrasound on the electrolyte reaches stability is recorded;
[0044] When the ultrasonic effect is stable, the ultrasound is turned off, and the time t2 when the electrochemical properties of the non-aqueous liquid flow battery electrolyte are restored to the state before the application of ultrasound is recorded;
[0045] After recovery, ultrasound is applied again, and the time t3 from the second application of ultrasound to reaching stability is recorded;
[0046] Analyzing the effect of intermittent application of ultrasound on the electrochemical properties of the non-aqueous liquid flow battery electrolyte according to the time t1, time t2, and time t3;
[0047] A comparative experiment of continuously applying ultrasound and intermittently applying ultrasound to the electrolyte of the non-aqueous liquid flow battery is carried out, and the best way to improve the performance of the non-aqueous liquid flow battery is analyzed based on the experimental results.
[0048] The specific steps of the test experiment in this embodiment are as follows:
[0049] Preparation of electrolyte
[0050] The deep eutectic solvent (DES) electrolyte components used in the experiment are: 1M choline chloride + 2M ethylene glycol. The configuration of DES requires that the two substances weighed in proportion be placed on a heated magnetic stirrer and stirred continuously at a constant temperature until the solution becomes clear and transparent. The configured DES needs to be cooled to room temperature in a sealed state. The components of the vanadium electrolyte are: anhydrous VCl3 + 30mLDES, with a concentration of 0.1M when the electrolyte is tested; and anhydrous VCl3 + 50mLDES, with a concentration of 0.1M when the full battery is tested. The components of the iron electrolyte are: anhydrous FeCl3 + 30mLDES, with a concentration of 0.1M when the electrolyte is tested; and anhydrous FeCl2 + 50mLDES, with a concentration of 0.1M when the full battery is tested. Since VCl3 dissolves slowly in DES, it is necessary to continue stirring until the solid matter is fully dissolved, there is no precipitation in the solution, and the solution becomes a uniform dark purple-red solution.
[0051] Experimental equipment
[0052] In the experiment, the electrolyte temperature was monitored in real time by a digital thermometer, and the water bath method was used to ensure that the electrolyte temperature was constant. The CV test was performed using an electrochemical workstation and a three-electrode system. The three electrodes in the three-electrode system were the working electrode (a glassy carbon electrode with an effective working diameter of 5 mm), the counter electrode (a platinum electrode), and the reference electrode (a saturated calomel electrode).
[0053] The data test of the whole battery is carried out by using the commercial Arbin BT 2000 (Arbin Instruments, USA). The main components of the battery are graphite felt electrodes (GFA series, Germany), sealing gasket (polytetrafluoroethylene), ion exchange membrane (Nafion 212, DuPont, USA), battery fixture (graphite), wherein the parallel flow field is distributed on the contact surface on the inner side of the battery fixture made of graphite.
[0054] Experimental procedures
[0055] Measurement of CV curve
[0056] (1) Electrode pretreatment: The working electrode was polished with 0.2 mm aluminum powder and then rinsed with deionized water. This operation should be repeated after each use.
[0057] (2) Preheating the electrolyte and electrodes. Place the electrolytic cell containing 30 mL of the prepared electrolyte in a constant temperature water bath to preheat to the required temperature for the experiment.
[0058] (3) Parameter setting. For FeCl3DES electrolyte, the scanning interval potential is: -0.35~0.85V; for VCl3DES electrolyte, the scanning interval potential is: -0.5~1.4V, both scanning in the positive direction. After the electrolyte is preheated, the three-electrode system is inserted into the electrolytic cell, and the potential scanning speed is 0.05V / s. Complete the above tests and record the obtained CV curve data.
[0059] Flow battery testing
[0060] (1) Pretreatment of carbon paper: Before the experiment, it is necessary to cut several square pieces of carbon paper with a size of 1 cm*1 cm and soak them in DES for a period of time.
[0061] (2) Preparation of electrolyte: The volume of the positive and negative electrolytes is 50 mL, and the concentration is 0.1 M.
[0062] (3) Treatment of Nafion membrane. A 1 cm*1 cm Nafion 212 membrane was heated in a water bath at 80°C, 5 wt.% H2O2 aqueous solution, 80°C ultrapure water, 80°C, 0.5 M H2SO4 solution, and 80°C ultrapure water for 1 hour. Finally, the membrane was immersed in a blank DES electrolyte for at least 12 hours.
[0063] (4) Battery assembly. The battery has a symmetrical structure. The Nafion212 membrane is used as a separator, and the components on both sides of the positive and negative electrodes are the same. After assembly, the device is fixed with screws.
[0064] (5) The glass container containing the electrolyte needs to be sealed with a rubber stopper to isolate it from the air, and a hose should be used to connect the electrolyte, peristaltic pump, and single battery.
[0065] Experimental Results and Discussion
[0066] The polarization curve of Fe-V redox non-aqueous flow battery at 25°C is shown in Figure 2 As shown by Figure 2 It can be seen that after adding ultrasound, the peak power density increased from 6.94 mW cm -2 Increased to 8.61mW·cm -2 , which increased by 24% compared with that without ultrasound, indicating that the polarization phenomenon inside the battery was alleviated. The limiting current density increased from 34.98 mA cm -2 Increased to 39.98 mA cm -2 , increased by 14.29%. According to the test results, the internal resistance of the battery without ultrasound and with ultrasound was 18.15ohm and 16.09ohm respectively. This shows that the addition of ultrasound can effectively reduce the internal resistance of the battery, improve the mass transfer inside the battery, and enhance the electrochemical performance.
[0067] Study on the duration of ultrasonic application and the intermittent application of ultrasonic waves
[0068] Three experiments are conducted in this section. Part I: For the newly prepared electrolyte, ultrasound is applied for the first time, and the time it takes for the effect of ultrasound on the electrolyte to stabilize is recorded. This experimental process is recorded as the TEST process, and the time it takes to stabilize after the first application is recorded as t1; Part II: When the ultrasonic effect is stable, turn off the ultrasound, record the time it takes for the electrolyte to stand and the electrochemical properties to recover to the state before ultrasound application. This experimental process is recorded as the REST process, and the time it takes for the electrolyte to stand is recorded as t2. Part III: The ultrasound is allowed to stand until it returns to the state before ultrasound application, and ultrasound is applied again to stabilize. This process is recorded as CONTINUE, and the time it takes to apply ultrasound again is recorded as t3. The above processes were explored for FeCl3 DES electrolyte and VCl3DES electrolyte respectively.
[0069] FeCl3 DES electrolyte
[0070] according to Figure 4 , CV curve of FeCl3DES electrolyte at 15℃, where Figure 4 (a)(b)(c) are the CV curves of TEST, REST and CONTINUE processes respectively. Figure 4 As shown in Figure 2a, as the ultrasonic application time increases from 0 min to 20 min, the peak current density (i pa and i pc ) increases. Under the condition of 15°C, when the ultrasonic application time reaches 12 minutes, the further increase of the ultrasonic action time does not cause the change of the redox reaction rate. Compared with the data when the ultrasonic application time is 20 minutes, it can be found that the cyclic voltammetry curves are almost the same. When the ultrasonic action stabilizes, the ultrasonic generator is turned off. As the electrolyte is left standing for a certain period of time, the present embodiment measures Figure 4 (b) shows the CV curve between the stop ultrasound time (electrolyte standing time) and the redox reaction. Within 3 minutes of ultrasound, the electrolyte still maintained good electrochemical properties. When the ultrasound was stopped for 11 minutes, the oxidation peak and reduction peak returned to the state before ultrasound was applied, and as the electrolyte standing time continued to increase, they remained in the state before ultrasound was applied. The stabilization effect was achieved after only 6 minutes of ultrasound application.
[0071] As the duration of ultrasonic action increases, the electrochemical performance improves, which is mainly related to the high viscosity of DES electrolyte. This may be because the accompanying effects of ultrasound, such as cavitation and mechanical action, destroy the internal chemical bonds of the electrolyte, and the disadvantage of DES electrolyte with high viscosity is improved. As the duration of ultrasonic action increases, energy accumulates continuously. The longer the ultrasonic action time, the stronger the mechanical effect and cavitation effect, and the more obvious the stirring and shearing effects, which leads to a continuous decrease in electrolyte viscosity and an increase in conductivity, which corresponds to the conductivity measurement results. The vibration of sound waves makes the charged particles in the electrolyte more evenly distributed. When the duration of ultrasonic action increases, the uniformity of particle distribution is better. However, this effect will not increase with the continuous increase of ultrasonic application time. Continuing to extend the ultrasonic action time cannot further improve the dispersion uniformity between charged particles.
[0072] The same experiment was performed at 25°C and 35°C, using the reconfigured electrolyte in the experiments under different conditions.
[0073] The EIS curves of FeCl3 DES electrolyte without ultrasound and with ultrasound of different power densities are shown in Figure 2. Figure 3 As shown. Figure 3 It can be seen that the curves in the figure have similar patterns, both of which are composed of a semicircle formed by the charge transfer process in the high-frequency region and a straight line formed by ion diffusion in the low-frequency region. It can be seen that at 25°C, as the ultrasonic power density increases, both the ohmic resistance and the charge transfer resistance decrease with the increase of the ultrasonic power density. In the absence of ultrasound, Rs and Rt are 96.75 ohms and 51.21 ohms respectively. When the ultrasonic power density reaches 0.28 W cm -2 When the temperature is increased, Rs and Rt decrease to 58.28 ohms and 29.19 ohms respectively. The results show that the addition of ultrasound can reduce the resistance loss of the DES electrolyte redox flow battery. The reduction of the electrochemical reaction resistance indicates that the charge transfer process of the electrolyte is accelerated, and the electrochemical reaction rate will be correspondingly accelerated.
[0074] contrast Figure 4(d), 5(d) and 6(d) show that as the temperature increases, the value of t1 gradually decreases, from 12min to 9min and 7min. The value of t2 gradually increases, that is, the lower the temperature, the longer it takes to achieve stability under ultrasound. After stopping ultrasound, low temperature conditions also have good timeliness. This is because the basic viscosity of the electrolyte is larger under low temperature conditions. Therefore, when the electrolyte temperature and ultrasonic power density remain unchanged, the time to reach the upper limit of the electrolyte viscosity will be shortened. In addition, when the basic viscosity of the electrolyte is small, the resistance encountered during ultrasonic propagation is also reduced, and energy is rapidly accumulated to change the physical properties of the electrolyte. The cavitation bubble shatters and causes instantaneous energy release. The impact of this process on the formation of the electrolyte is the main mechanism of ultrasound to improve the electrochemical and physical properties. During the time from the formation of the cavitation bubble to the shattering of the cavitation bubble, the energy also completes the process from accumulation to reaching the cavitation bubble storage limit and then to release. When the basic viscosity of the electrolyte is small, ultrasound can form a sufficient number of cavitation bubbles in the electrolyte in a relatively short time, thereby increasing the number of times the charged particles are impacted. Therefore, the duration of ultrasound is also one of the factors that affect the performance of the electrolyte, which can improve the electrochemical and physical properties of the electrolyte. However, compared with the two factors of ultrasonic frequency and power, the effect of extending the ultrasonic treatment time on the performance of the electrolyte is not obvious enough. Prolonging the ultrasonic time can. Although extending the duration of ultrasound acting on the electrolyte can ensure more complete ultrasonic treatment, in practical applications, the effects of ultrasound on the internal structure of the battery, as well as the loss of battery component materials and ultrasonic energy consumption must be considered. Continuously extending the duration of ultrasound action will hardly make the battery performance more significantly improved, but will be detrimental to energy and economic savings.
[0075] The relationship between the peak values of the oxidation peak and the reduction peak of the three processes and the process time, such as Figure 7 At the same temperature, the value of t1 is close to the value of t2, while the value of t3 is significantly smaller than t1. That is to say, for the newly prepared electrolyte, ultrasound needs to act for a longer time to achieve a good and stable effect, and re-application of ultrasound will reach stability at a faster speed. This has important research significance for the intermittent application of ultrasound. In actual applications, when using the prepared electrolyte, it takes a longer time, and when it is applied again, the action time is greatly shortened, which greatly reduces energy consumption.
[0076] VCl3 DES electrolyte
[0077] Similar to the above experimental process, a series of experiments were also carried out on VCl3 DES electrolyte. Figure 8The cyclic voltammetry curve of VCl3 DES electrolyte at 15°C is similar to the test results of FeCl3 DES electrolyte. For the TEST process, as the ultrasonic duration increases, the peak current density of the oxidation peak and the reduction peak increases. In the REST process, as the electrolyte rest time increases, the peak current density of the oxidation peak and the reduction peak decreases. When ultrasound is applied again, the duration of ultrasound action within a certain period of time is still the same as i pa and i pc For the three processes, when the time length reaches a certain value, the change of time will no longer cause the change of the electrochemical reaction process. pa Under the condition of 15°C, when the ultrasonic application time reaches 15 minutes, the further increase of the ultrasonic action time will not cause the change of the redox reaction rate, which is almost the same as the CV curve when the ultrasonic application time reaches 20 minutes. Figure 8 In (b), the CV curve between the time after stopping ultrasound and the redox reaction shows that the electrochemical performance almost returned to the initial state 16 minutes after ultrasound was stopped. The value of t2 is almost equal to the value of t1, while the value of t3 is significantly smaller than the value of t1.
[0078] At 25℃ and 35℃, the experiment at 15℃ was repeated with the newly configured electrolyte. The change in temperature changed the initial electrolyte of the electrolyte. The resistance of charged particles at different temperatures was different, and the propagation process of ultrasound was also different. As the temperature increased, t1 changed from 15min at 15℃ to 11min at 35℃, t2 changed from 16min at 15℃ to 10min, and t3 changed from 11min at 15℃ to 8min. In addition, compared with FeCl3DES electrolyte ( Figure 4 (d), 5(d) and 6(d)) and VCl3 DES electrolyte ( Figure 8(d), 9(d) and 10(d)) have t1, t2, t3, and the temperature is the same. The time required for ultrasound to act on VCl3 DES electrolyte is longer than that for FeCl3 DES electrolyte. The timeliness of ultrasound acting on the electrolyte is also better for VCl3 DES electrolyte than for FeCl3 DES electrolyte. This difference between the two electrolytes may be related to the ionic radius of iron ions and vanadium ions. The ionic radius of vanadium ions is slightly larger than that of iron ions, and more energy accumulation is required to make vanadium ions reach the same movement rate as iron ions. When actually used in non-aqueous flow batteries, longer t1, t3 values and shorter t2 values should be used as references for the duration of intermittent ultrasound. Taking 25℃ as an example, when intermittent ultrasound is applied to Fe-VDES electrolyte, for the newly assembled electrolyte, ultrasound needs to be applied for 12 minutes, ultrasound stopped for 9 minutes, and then ultrasound applied for 9 minutes, and then ultrasound is applied cyclically according to the operation of stopping for 9 minutes and applying for 9 minutes.
[0079] Full battery test
[0080] Based on the above experimental results, a comparative test of continuous ultrasound and intermittent ultrasound was conducted on the Fe-VDES flow battery at 25°C. Two identical batteries with the same positive and negative electrolytes were used. One group was continuously subjected to 0.11 W·cm -2 Ultrasound was applied to another group of assembled batteries in a cycle of 9 minutes of stop and 9 minutes of application. Constant current charge and discharge experiments were carried out, with the charge and discharge time being 30 minutes respectively. Fig.11 In the three charge-discharge cycle tests, the charging voltage and discharging voltage of intermittent ultrasound are close to those of continuous ultrasound. According to the energy efficiency data in Table 1, intermittent ultrasound still maintains a high energy efficiency when the energy consumption is reduced by half.
[0081] Table 1
[0082]
[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for improving the performance and energy efficiency of non-aqueous liquid flow batteries using ultrasound, characterized in that: The following steps are involved: A non-aqueous liquid flow battery electrolyte is prepared, ultrasound is applied to the non-aqueous liquid flow battery electrolyte for the first time, and the time t1 when the effect of ultrasound on the electrolyte reaches stability is recorded; When the ultrasonic effect is stable, the ultrasound is turned off, and the time t2 when the electrochemical properties of the non-aqueous liquid flow battery electrolyte are restored to the state before the application of ultrasound is recorded; After recovery, ultrasound is applied again, and the time t3 from the second application of ultrasound to reaching stability is recorded; Analyzing the effect of intermittent application of ultrasound on the electrochemical properties of the non-aqueous liquid flow battery electrolyte according to the time t1, time t2, and time t3; A comparative experiment of continuously applying ultrasound and intermittently applying ultrasound to the electrolyte of the non-aqueous liquid flow battery is carried out, and the best way to improve the performance of the non-aqueous liquid flow battery is analyzed based on the experimental results.
2. The method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound according to claim 1, characterized in that: The time t2 when the electrochemical performance of the electrolyte of the non-aqueous flow battery recovers to the state before the application of ultrasound is greater than or equal to the time t1 when the effect of ultrasound on the electrolyte reaches stability.
3. The method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound according to claim 1, characterized in that: The types of non-aqueous liquid flow battery electrolytes include FeCl3DES electrolyte and VCl3DES electrolyte.
4. The method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound according to claim 1, characterized in that: The electrolyte components of the non-aqueous liquid flow battery electrolyte include choline chloride and ethylene glycol; Place choline chloride and ethylene glycol weighed in proportion on a heated magnetic stirrer, stir continuously at a constant temperature until the solution becomes clear and transparent, and cool to room temperature in a sealed state; The amount and concentration of the electrolyte are set according to the type of non-aqueous flow battery electrolyte being tested.
5. The method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound according to claim 1, characterized in that: The process of analyzing the electrochemical performance of the non-aqueous liquid flow battery electrolyte according to the time t1, the time t2, and the time t3 includes: Obtaining a CV curve of the electrolyte of the non-aqueous liquid flow battery, analyzing the change of the redox reaction rate of the non-aqueous liquid flow battery with the duration of ultrasonic action based on the CV curve, and then obtaining the cause of the change of the electrochemical performance of the electrolyte of the non-aqueous liquid flow battery; The relationship between the peak values of the oxidation peak and the reduction peak and the process time during the ultrasonic application test is constructed to determine the size of the oxidation peak corresponding to different test times, and then to determine the impact of ultrasound on the electrochemical performance of non-aqueous flow batteries.
6. The method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound according to claim 5, characterized in that: The process of obtaining the CV curve of the non-aqueous liquid flow battery electrolyte comprises: The surface of the working electrode was polished using aluminum powder with a particle size of 0.2 mm and then rinsed with deionized water; Place the electrolytic cell after the electrolyte is prepared in a constant temperature water bath and preheat it to the required temperature for the experiment; The scanning interval potential and potential scanning speed were set according to the electrolyte type, the three-electrode system was inserted into the electrolytic cell for CV testing, and the CV curve data was recorded.
7. The method of using ultrasound to improve the performance and energy efficiency of non-aqueous flow batteries according to claim 1, characterized in that: During the process of applying ultrasound to the non-aqueous flow battery electrolyte, a digital thermometer is used to monitor the electrolyte temperature in real time, a water bath method is used to keep the electrolyte temperature constant, and a CV test is performed using an electrochemical workstation and a three-electrode system, wherein the three-electrode system includes a working electrode, a counter electrode, and a reference electrode.
8. The method of using ultrasound to improve the performance and energy efficiency of non-aqueous flow batteries according to claim 1, characterized in that: The process of conducting a comparative experiment of continuously applying ultrasonic waves and intermittently applying ultrasonic waves to the electrolyte of the non-aqueous liquid flow battery includes: The experimental temperature and time are set, and constant current charge and discharge experiments with continuous ultrasound and intermittent ultrasound are carried out on two identical non-aqueous liquid flow batteries using the same positive and negative electrode electrolytes, and energy efficiency data of the non-aqueous liquid flow batteries are obtained respectively. Based on the energy efficiency data, the electrochemical performance of the non-aqueous liquid flow batteries under continuous ultrasound and intermittent ultrasound are compared.
9. The method of using ultrasound to improve the performance and energy efficiency of non-aqueous flow batteries according to claim 1, characterized in that: The experimental equipment of the comparative experiment includes: a graphite felt electrode, a sealing gasket, an ion exchange membrane, and a battery fixture, and a parallel flow field is distributed on the contact surface inside the battery fixture.
10. The method for improving the performance and energy efficiency of non-aqueous flow batteries using ultrasound according to claim 1, characterized in that: During the comparative experiment, the ion exchange membrane was heated in H2O2 aqueous solution, ultrapure aqueous solution, H2SO4 solution and ultrapure aqueous solution for 1 hour in sequence, and then immersed in a blank electrolyte for at least 12 hours.
